Analysis of the influence of yarn angle on the mechanical behaviors of cured woven composites. (November 2020) - Liang, Biao; Zhang, Weizhao; Gao, Sasa
Manufacturing process would modify the yarn angle of woven composites. To have a high-fidelity mechanical analysis, it is necessary to study its potential impact. In this article, experimental tests were specifically designed and conducted to investigate the influence of yarn angle on the mechanical behaviors of cured woven composites. The results show that yarn angle variation has a significant impact on the elastic modulus, Poisson's ratio, and yield stress. The tensile deformation along yarn directions and shear deformation between two yarns were also investigated and their coupling with yarn angle variation was analyzed. It shows that when the yarn angle variation (from 90°) is less than 10°, the influence of the tension–shear coupling on the tensile behavior along yarn directions and shear behavior between two yarn directions is small and can be neglected. When the yarn angle variation is more than 20°, the influence of tension–shear coupling is significant and must be accounted for in constructing the constitutive law for the cured non-orthogonal woven composites.